2021
DOI: 10.3390/cells10123556
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Pancreatic Cancer In Vitro and In Vivo via Modulation of Nrf2 and NF-κB Signaling Pathways by Natural Compounds

Abstract: Pancreatic cancer is a disease in which deregulation of signaling pathways plays a key role, thus searching for their novel modulators is a promising therapeutic strategy. Hence, in this study, the effect of phytochemical combinations on the canonical and non-canonical activation of Nrf2 and its interaction with the NF-κB pathway was evaluated in extensively proliferating pancreatic cancer cell line, PSN-1, in comparison to non-cancerous MS1 cells. The activation of Nrf2 and NF-κB, expression of their target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…These compounds exhibited anticarcinogenic activities in in vivo experiments [24][25][26][27][28][29][30][31][32] or on human colon cancer cells [33]. PEITC also exhibited anticarcinogenic activities [34][35][36]. Thus, these results should be investigated further for the anticarcinogenic properties of BUITC and PEN in in vivo experiments.…”
Section: Antimutagenic Effect Of Compounds 1-3mentioning
confidence: 99%
“…These compounds exhibited anticarcinogenic activities in in vivo experiments [24][25][26][27][28][29][30][31][32] or on human colon cancer cells [33]. PEITC also exhibited anticarcinogenic activities [34][35][36]. Thus, these results should be investigated further for the anticarcinogenic properties of BUITC and PEN in in vivo experiments.…”
Section: Antimutagenic Effect Of Compounds 1-3mentioning
confidence: 99%
“…In addition, cellular processes, including apoptosis, ferroptosis, necroptosis ( 29 ), and autophagy ( 30 ), have been shown to affect the tumor immune microenvironment of pancreatic adenocarcinoma. Multiple signal transduction pathways, including Wnt ( 31 ), vascular endothelial growth factor (VEGF) ( 32 ), transforming growth factor (TGF)-beta ( 31 ), PI3K-Akt ( 33 ), nuclear factor (NF)-kappa B ( 34 ) and hedgehog ( 35 ), have been shown to participate in the growth and metastasis of pancreatic adenocarcinoma and may be associated with immune infiltration. Based on the experimental outcome and prognostic significance, hub genes downstream of Th2 cells were investigated to explore their role in immunity, metabolism, cellular processes and signal transduction.…”
Section: Resultsmentioning
confidence: 99%
“…could inhibit the PSN-1 cell growth with an IC 50 46 µM and inhibit the MS1 cell growth with an IC 50 49 µM. This combination could greatly reduce the expression of NF-κB p65 subunits, and activate Nrf2 and downstream genes as GSTP, NQO1, and SOD in PANC-1 cells ( Krajka-Kuźniak et al, 2020 ) and PSN-1 cells ( Cykowiak et al, 2021 ). Further investigation revealed that the combination of xanthohumol (40 mg/kg) and phenethyl isothiocyanate (15 mg/kg) could inhibit the plasma COX-2 and nuclear STAT3 expression ( Cykowiak et al, 2021 ).…”
Section: Natural Products Undergoing Clinical Evaluation In Pancreati...mentioning
confidence: 99%